Analisis mutu pelayanan kesehatan menggunakan metode Servperf dan IPA pada pasien rawat jalan di Rumah Sakit Islam Malahayati Medan - Anastasya, Raihanis; Gurning, Fitriani Pramita (TROPHICO: Tropical Public Health J., 2023)
When it comes to satisfying customers whose requirements are becoming more varied over time, quality of service in a business network is a key factor. Patients at Malahayati Islamic Hospital Medan continue to have concerns regarding the quality of care they get and the WOTJ quality indicator, which now stands at 55% instead of the target 100%. The goal of this study is to use the Servperf and IPA techniques to examine the degree of outpatient satisfaction at Malahayati Islamic Hospital Medan along the categories of tangibles, dependability, responsiveness, assurance, and emphasizing. A quantitative survey with a cross-sectional design was used for this study. This research used purposive sampling to collect data from a representative sample of 96 outpatients from Hospital in Medan. Based on the findings of this research, Malahayati Islamic Hospital Medan can enhance the quality of its outpatient treatment by focusing on three specific service aspects. The waiting area and exam rooms need to be more relaxing, drugs should be delivered quickly, and the doctors and other personnel should be more personable. Prescriptions for both outpatient and inpatient use must enter the pharmacy via different entrances to prevent a backlog.